A BRIEF HISTORY OF POST-ISLAMIC RELATIONS BETWEEN IRAN AND THE SUBCONTINENT - Dr Aqsa Sajid; Dr Zaheer Hasan Watto; Dr Sabina Awais (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
After the emergence of Islam, the relations between the two Aryan nations of Iran and India became stronger than in ancient times. These stable connections began in the Ghaznavid period when Mahmud conquered India and a large number of Iranian scholars, writers and poets visited the land of the subcontinent. After the Ghaznavids, the Ghoris also took keen interest in the promotion of Persian language and literature in the subcontinent. These good relations continued during the Khilji, Tughluq, Lodhi and Bahmani periods. The Mughal period is called the Golden Age in terms of relations between Iran and the subcontinent. After the partition of India, Iran's fraternal ties with India, Pakistan and Bangladesh have been maintained on the basis of peaceful coexistence.